The hymns of Luke's infancy narratives their origin, meaning and significance - Farris, Stephen (Sheffield : JSOT, 1985)
"These hymns, the Magnificat, Benedictus and Nunc Dimittis, are a familiar part of Christian liturgy; but their origin is uncertain, their meaning debated and their significance within Luke-Acts often ignored. This monograph argues that they were composed in Hebrew by Jewish-Christian poets, and were incorporated by the evangelist as anticipating certain key themes of his own work."--Bloomsbury Publishing.
Includes index.
Bibliography: p. 200-210.
Also issued in print.
Electronic reproduction.
Keywords: Bible. -- Commentaries; Canticles